COVID-19 Related Distress in Gambling Disorder - Salerno, Luana; Pallanti, Stefano (Frontiers in Psychiatry, 2021)
Abstract The COVID-19 pandemic has exerted a dramatic impact on everyday life globally. In this context, it has been reported that the lockdown and social distancing may have exerted an impact even on gambling behavior, not only by increasing gambling behavior in those affected by this disorder but even contributing to the occurrence of new cases. To explore such a possibility, we designed a cross-sectional web survey addressing a general population sample that lasted three weeks (March 23 to April 20). Participants completed a survey including a demographic information section, a question regarding the presence of pathological gambling in the past and several questionnaires. These included the Perceived Stress Scale (PSS), the Kellner’s Symptom Questionnaire (SQ), and the version of The Yale Brown Obsessive Compulsive Scale adapted for Pathological Gambling (PG-YBOCS) that investigated the presence of gambling behaviors in the last week. The final sample was composed by 254 subjects (112 males, 44.1%; 142 females, 55.9%). According to PG-YBOCS total score, pathological gambling has been found in 23.6% (n=60) of the sample (53 males, 88.3%; 7 females, 11.7%), which is a high frequency compared to that reported by the existing literature. Among gamblers, 20.9% (n=53) reported both past and current problem gambling (they have been defined as “chronic gamblers”), whereas 2.8% (n=7) did not report to use gambling platforms in the past but only in the last week (defined as “new gamblers)”. Data analysis showed a statistically significant difference between gamblers and people who do not gamble in age but not in education, and higher level of perceived stress, distress and hostility in both chronic and new gamblers compared to those who did not report gambling behavior. A consistent proportion of business owners and unemployed individuals reported problem gambling during the lockdown period.